(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
We investigate a new graph which is called Step Grid Graph. We prove that the step grid graph is graceful. We have investigate some step grid graph related families of connected graceful graphs. We prove that path union of step grid graph,cycle of step grid graph and star of step grid graph are graceful graphs.